Characteristics of karst caves inferred from microtremor studies: A case study from Cerme Cave, Yogyakarta, Indonesia - Yuliyanto, Gatot; Muhammad Irham Nurwidyanto (Acta Carsologica, 2023)
A microtremor survey based on ground surface data acquisition was used to identify and characterize the karst area of Cerme Cave, Yogyakarta, Indonesia, from the entrance to the exit of the cave. The entrance and exit of the cave are used as tie-in points because the characteristics of the two locations can be directly observed. Parameters used in this study include ground vibration amplification, shear wave velocity, and Poisson’s ratio. The presence of cavities can be characterized by a relatively strong contrast between these physical parameters and their surroundings. The exit of the cave, which can be considered as a sinkhole, has a dominant frequency of 3.2 to 4.6 Hz, which is relatively higher than that of the surrounding area. At the entrance of Cerme Cave, which has a large cavity, a small ground vibration amplification was detected, less than 0.1. The entrance and exit of the cave also exhibit a low shear wave propagation velocity of less than 350 m/s. The presence of a subsurface fluvial channel in Cerme Cave can be characterized by a high Poisson’s ratio of 0.4–0.5, a gain value of less than 0.1, and a shear wave velocity of less than 350 m/s.